APPLICATION OF JOB SATISFACTION SURVEY IN TELEMARKETING OPERATORS IN BRAZIL - Honorato, Antonio Edson Oliveira; Oliveira, Agostinha Mafalda Barra de (Brazilian Journal of Production Engineering, 2018)
Job satisfaction is an important variable within the organization, as it directly reflects its productive capacities and production quality levels. Due to several factors, internal or external, the organization can suffer considerable losses in the level of satisfaction of its employees; and when low, this satisfaction can cause great losses not only from an administrative, productive and functional point of view, but also in the health and well-being of the people. In Brazil, there is a specific sector that calls attention to its rapid growth; the service sector. In this one, telemarketing stands out, not only due to the large number of employees, but also due to the increase of occupational diseases developed by professionals working in it. Considering these facts, the objective of this study was to measure and analyze, through the Job Satisfaction Survey (JSS), the level of satisfaction of the telemarketing operators of a Brazilian contact center, since these are the main ones affected by the negative load inherent in the performance of its functions. The survey was attended by 188 telemarketers. The results presented the employee’s dissatisfaction in several aspects, such as payment, benefits and contingent rewards. It can be concluded at the end of the research, that there is a great need for companies in this sector – that employ more than 1.6 million people in Brazil – to work and develop methods so that their employees feel satisfied and motivated by the work they perform. Mainly, to reduce the health risks faced by this working class.